The Influence of Musical Style in Perceived Emotion - Tizón Díaz, Manuel; Gómez Martín, Francisco (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2020)
In this work we address the problem of understanding how musical style influences perceived emotion as well as their pedagogical consequences. The first problem arises when considering the very definition of style. The definition of musical style and how to apply it is thoroughly discussed. Several experiments were carried out in order to gain understanding about the emotional response to musical style. Six styles (Baroque, Classicism, Romanticism, pandiatonicism, twelve-tone serialism, and Phrygian mode) were selected and pieces were composed in those styles to be later played to both musicians and novices. Their perceived emotional response was measured and the results were analyzed thereafter. Differences were found across styles, mode and musical background, including complex patterns in valence and arousal. Last but not least, the knowledge acquired from this research can be incorporated a corpus for application and future study and use in music conservatories and centers for higher education and investigation.
Keywords: Musical Style; emotions; cognition; musical composition